Vaccination Coverages Among Splenectomized Patients: A Retrospective Study from an Italian Southern Province - Giuseppe Di Martino; Riccardo Mazzocca; Tania Masci; Lisa Berghella; Jacopo Del Papa; Francesco D’Aloisio; Mario Messinese; Fabrizio Cedrone; Patrizia Marani Toro; Graziella Soldato (Vaccines)
Background: Splenectomized patients have a higher risk compared to the general population of developing post-splenectomy infection, particularly by capsulated bacteria. Splenectomized patients need to be vaccinated against pneumococcal diseases, meningococcal disease, and heamophilus influenzae (Hib) in order to avoid invasive bacterial diseases. This study evaluated vaccination coverages among splenectomized patients in a Southern Italian province. Methods: A retrospective study was conducted evaluating all splenectomized patients from the Pescara province from 2015 to 2023. Vaccination coverages were calculated before and after splenectomy for the following vaccines: pneumococcal disease, meningococcal disease, Hib, and COVID-19. Results: A total of 97 patients were considered during the study period. Vaccination coverages were low before surgery, but they increased after splenectomy. Higher coverages were found against pneumococcal diseases (77.3%), meninigococcal disease (58.8%), and COVID-19 (91.8%). Conclusions: Vaccination coverages among splenectomized patients in the Pescara province are not satisfying. It is imperative to implement educational measures for patients and physicians to increase vaccination coverages.